Settlement of Double Certificate Cases in Bandung (Case Study of Judge’s Decision Number: 976k/Pdt/2015) - Soediro, Soediro; Faridli, Efi Miftah; Dwiana, Dhea Anggit (Jurnal Dinamika Hukum, 2021)
One of the objectives of the Basic Agrarian Law (UUPA) is to provide legal certainty for all people and enable the functioning of earth, air, and space, as well as natural wealth that aspired. However, the Basic Agrarian Law (UUPA) has not provided legal certainty over land, one of which is a plot of land with more than one certificate with the same object. The factors causing the occurrence of multiple certificates are caused by the community and the government from the National Land Agency, which does not have a valid database as referred to by Supreme Court Decision Number 976 K/PDT/2015. The formulation of the problem in this research is how efforts to prevent the occurrence of multiple certificates (overlapping) and what are the obstacles in preventing their occurrence double certificate (overlapping). This research aims to determine and analyze the prevention efforts and constraints in preventing the occurrence of double certificates (overlapping). The problems in this study were studied using a normative juridical method using a statutory approach and a conceptual approach—data collection techniques using studies bibliography and assistance and defense of legal facts. According to the research findings, efforts to prevent the occurrence of double certificates (overlapping), specifically by optimizing administration land use and creating land registration maps, so that if there are indications of the occurrence of double certificates, they can be canceled as soon as possible, as well as obstacles in preventing double certificates (Overlapping), specifically the lack of understanding and enthusiasm from the community in applying for their land in Complete Systematic Land Registration (Pendaftaran Tanah Sistematis Lengkap, PTSL), are shown.Keywords: Double certificate; legal certainty; overlapping.